Theoretical and Computational Investigations of Nanoparticle–Biomembrane Interactions in Cellular Delivery. Issue 9 (11th November 2014) - Ding, Hong‐ming; Ma, Yu‐qiang
Abstract : With the rapid development of nanotechnology, nanoparticles have been widely used in many applications such as phototherapy, cell imaging, and drug/gene delivery. A better understanding of how nanoparticles interact with bio‐system (especially cells) is of great importance for their potential biomedical applications. In this review, the current status and perspective of theoretical and computational investigations is presented on the nanoparticle‐biomembrane interactions in cellular delivery. In particular, the determining parameters (including the properties of nanoparticles, cell membranes and environments) that govern the cellular uptake of nanoparticles (direct penetration and endocytosis) are discussed. Further, some special attention is paid to their interactions beyond the translocation of nanoparticles across membranes (e.g., nanoparticles escaping from endosome and entering into nucleus). Finally, a summary is given, and the challenging problems of this field in the future are identified. Abstract : Nanoparticles have recently been widely used as drug delivery carriers. This review summarizes the recent progresses on the theoretical and computational investigations of nanoparticle‐biomembrane interactions in cellular delivery. The factors that govern cellular uptake of nanoparticles are discussed in detail, and their interactions in intracellular trafficking are also illustrated. Finally, the challenging problems of this field in the future are given.